Parenting styles for children with oppositional defiant disorder: Scope review - Maryam Fooladvand; Mohammad Ali Nadi; Ahmad Abedi; Ilnaz Sajjadian (Wolters Kluwer Medknow Publications, 2021)
Behavioral and emotional problems are the most common form of child psychiatric pathology. Parenting styles are one of the factors affecting the formation of children's personality and the use of inefficient styles can lead to several negative consequences such as behavioral problems. The aim of the present article is to describe a variety of parenting styles and their relationship with children behavioral problems. The present study reviews a variety of parenting styles including Kazdin's Parent Management Education Model, Barclay's Parent Training Program, Adler and Dreikurs Approach, and Positive Parenting Program. Finally, based on reality theory, parenting is neglected to be one of those styles. Therefore, it is imperative to do a research based on reality theory with existential psychotherapy and with the view that everyone chooses to behave, external pressure is always an imposition, the children learn from their mistakes, and everyone is responsible for his own happiness.